2011
DOI: 10.1002/hed.21686
|View full text |Cite
|
Sign up to set email alerts
|

Transoral laser surgery versus radiotherapy: Systematic review and meta‐analysis for treatment options of T1a glottic cancer

Abstract: The approach for optimal treatment of T1a glottic cancer remains unanswered. This results from the relatively inconclusive evidence obtained from the current literature. Properly designed, prospective, randomized, or well-controlled studies will be required. Similar methodologies for treatment and reporting need to be established to make a valid and meaningful comparison between studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
126
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(140 citation statements)
references
References 33 publications
9
126
0
5
Order By: Relevance
“…Results are often difficult to compare among studies because of the absence of standardization of measurements, the wide range of values that can be considered in the normal range, a significant intraand interindividual variability in these measurements, and the various computer programs used. 27 In the 8 studies retained for the meta-analysis published by Abdurehim and colleagues, 10 in the TLM groups, jitter ranged from 0.74 AE 1 to 8.67 AE 2.63, and shimmer from 1.31 AE .25 to 13.4 AE 1. In most publications of acoustic analysis, a jitter value of less than 1% and a shimmer value of less than 3.8% are considered normal, and beyond these values voice may be considered pathologic.…”
Section: What Are the Objective Acoustic Results After Transoral Lasementioning
confidence: 99%
“…Results are often difficult to compare among studies because of the absence of standardization of measurements, the wide range of values that can be considered in the normal range, a significant intraand interindividual variability in these measurements, and the various computer programs used. 27 In the 8 studies retained for the meta-analysis published by Abdurehim and colleagues, 10 in the TLM groups, jitter ranged from 0.74 AE 1 to 8.67 AE 2.63, and shimmer from 1.31 AE .25 to 13.4 AE 1. In most publications of acoustic analysis, a jitter value of less than 1% and a shimmer value of less than 3.8% are considered normal, and beyond these values voice may be considered pathologic.…”
Section: What Are the Objective Acoustic Results After Transoral Lasementioning
confidence: 99%
“…The meta-analysis published by Feng and colleagues 82 in 2011 included 5 studies reporting local control rates of T1-T2 glottic cancer and found no significant difference between the treatment modalities. Finally, Abdurehim and colleagues 83 included 10 studies in their meta-analysis of oncologic outcomes for T1a glottic cancer and found no difference between TLM and RT with regard to local control, disease-specific survival, or overall survival. Thus, for Tis, T1, and T2 glottic carcinoma, there is currently no evidence showing a difference in local control, diseasespecific survival, or organ preservation for either surgery or RT.…”
Section: Evaluation Of Outcomementioning
confidence: 97%
“…8 However, there is still considerable debate regarding expected voice outcomes, [9][10][11][12] with widely varying opinion among health care providers on which modality offers the best voice outcome. 10 Despite the postoperative voice playing a significant role in treatment decision making, there is no consistent voice profile after TLM. [8][9][10] Acoustic measures of perturbation and noise have been widely used to investigate voice outcomes after TLM.…”
Section: Introductionmentioning
confidence: 99%
“…10 Despite the postoperative voice playing a significant role in treatment decision making, there is no consistent voice profile after TLM. [8][9][10] Acoustic measures of perturbation and noise have been widely used to investigate voice outcomes after TLM. 11 Perturbation measures calculate the cycle-to-cycle variations in fundamental frequency (jitter) and amplitude (shimmer) 13 and are linked to impaired vocal fold movement 14 and the perceptual quality of vocal hoarseness.…”
Section: Introductionmentioning
confidence: 99%